Mathematical Reasoning Analysis in Solving Limit Functions Problems of Students in Mathematics Education of Pare-pare Muhammadiyah University - Asdar Dollo (Department of Mathematics Education University of Muhammadiyah Malang, 2018)
This research aimed to describe the students‘ reason in solving theproblem of limit function and comparation between high-ability subject(HS) and medium-ability subject (MS). The instrument in this research wasthe researcher himself as the main instrument guided by the task limitfunction and valid interview guidelines. Data collection was done by taskbasedinterviews. The subjects of the study were V-semester studentsconsisting of 2 students (1 subject is having high ability and 1 subject ishaving medium ability). The research process followed the steps of: (a)formulating the mathematical reasoning indicator in solving the problem oflimit function based on theory, (b) formulating the supporting instrument(task limit function and interviewing guide), (c) taking the research subject,(d) taking the data to tell the students‘ reasoning in solving the limit functiontests (f) conducting analysis of mathematical reasoning data of the studentsin solving the problem of function limit, (g) conducting discussion ofanalysis result, (h) concluding the research results. The result of the researchshowed that 1) the reasoning equation of the high-ability subject (HS) andthe medium ability subject (MS) in solving the function limit problem wasto do inductive reasoning first then perform deductive reasoning, 2)difference of reasoning subject with high ability (HS) medium ability (MS)in solving the problem of function limit was only in terms of mathematicalreasoning process.